Navigational features of dove flights in the gravity field of Ukraine - V. I. Starostenko; V. A. Kanevskiy; V. A. Entin; O. B. Gintov; S. I. Guskov; E. D. Morenkov; N. Blaser; V. Meskenight; G. P. Lipp (Геофизический журнал, 2012)
Results of test flights of domestic doves in the flat country of Ukraine characterized by partitioned gravity field (Buge anomalies from -30 to +70 mGal) have been considered. The length of flights from starting point to the place of permanent location was from 15 to 200 km. The routes were tracked trough weakly and strongly divided gravity field. Both local experienced birds and young ones specially bred in outlying gravity fields took part in the flights. GPS sensors were fastened on birds fixing coordinates of flight (ϕ, λ, H) in every 1 sec. Test results demonstrated with other factors (roads, rivers et al.) that gravity anomalies even small ones (±1-2 mGal) produce deviation of dove tracks from the straight line together. It is urgent to continue the experiment which will be corrected taking into account the experience obtained. Inertial-gravitational mechanism of animal navigation has been suggested.